Factors associated with elevated SARS-CoV-2 immune response in children and adolescents - Messiah, Sarah E.; Abbas, Rhiana; Bergqvist, Emma; Kohl, Harold W.; Swartz, Michael D.; Talebi, Yashar; Sabharwal, Rachit; Han, Haoting; Valerio-Shewmaker, Melissa A.; DeSantis, Stacia M.; Yaseen, Ashraf; Gandhi, Henal A.; et al. (Frontiers in Pediatrics, 2024)
Background: Understanding the distinct immunologic responses to SARS-CoV-2 infection among pediatric populations is pivotal in navigating the COVID-19 pandemic and informing future public health strategies. This study aimed to identify factors associated with heightened antibody responses in children and adolescents to identify potential unique immune dynamics in this population.Methods: Data collected between July and December 2023 from the Texas Coronavirus Antibody REsponse Survey (Texas CARES), a statewide prospective population-based antibody survey among 1-to-19-year-old participants, were analyzed. Each participant had the following data available for analysis: (1) Roche Elecsys® Anti-SARS-CoV-2 Immunoassay for Nucleocapsid protein antibodies (Roche N-test), (2) qualitative and semi-quantitative detection of antibodies to the SARS CoV-2 spike protein receptor binding domain (Roche S-test), and (3) self-reported antigen/PCR COVID-19 test results, vaccination, and health status. Statistical analysis identified associations between participant characteristics and spike antibody quartile group.The analytical sample consisted of 411 participants (mean age 12.2 years, 50.6% female). Spike antibody values ranged from a low of 6.3 U/ml in the lowest quartile to a maximum of 203132.0 U/ml in the highest quartile in the aggregate sample. Older age at test date (OR=1.22, 95% CI: 1.12, 1.35, p< .001) and vaccination status (primary series/partially vaccinated, one or multiple boosters) showed significantly higher odds of being in the highest spike antibody quartile compared to younger age and unvaccinated status. Conversely, fewer days since the last immunity challenge showed decreased odds (OR=0.98, 95% CI: 0.96, 0.99, p=0.002) of being in the highest spike antibody quartile versus more days since last immunity challenge. Additionally, one out of every three COVID-19 infections were asymptomatic.Older age, duration since the last immunity challenge (vaccine or infection), and vaccination status were associated with heightened spike antibody responses, highlighting the nuanced immune dynamics in the pediatric population. A significant proportion of children/adolescents continue to have asymptomatic infection, which has important public health implications.